AS REDES SOCIAIS NA INTERNET, O COMPARTILHAMENTO DE INFORMAÇÕES E A ADERÊNCIA AO CONSUMO CONSCIENTE: UM ESTUDO EXPLORATÓRIO NA REGIÃO DO GRANDE ABC PAULISTA - Fioravanzo, Cristiane Maravelli (2013)
Allied to studies about sustainability, there are numerous discussions and attitudes to oppose the consequences of the irrational use of the planet s natural resources. And out of them comes the understanding of the consumption, its influences and alternatives. An individual may have consumerist or ethical consumption habits. The consumerist is seen as having the opposite of the ethical consumer s habits, being led to a purchase by impulse or stimuli, without considering his or her needs, or future impact. The consumption is, in fact, necessary to mankind. However, when it is done exaggeratedly and incorrectly, it may cause serious social and/or environmental consequences. The ethical consumer is able to ponder the existing possibilities, the impact that may be caused by the acquisition, in order to minimize its consequences, and somehow contribute to a more sustainable society. The main goal of this research is to comprehend the researchers adherence to the behavior of the ethical consumerism, as well as evaluate how people who are part of internet social networks share information about this topic, considering that the internet is one of the main means of communication and sharing information. For the research, the methodology of qualitative analysis of exploratory character was used, as well as the technique of research in depth, based on semi-structured questionnaire. Through the analysis of the content, the understanding of the results shows that all of the interviewed have a certain degree of knowledge about ethical consumerism, and the majority tries to have some kind of ethical attitude. Still, these individuals may suffer some influence in the process, especially on a personal character, which leads to an alteration of attitude. In relation to how the information about the topic is shared on the internet, it was possible to see that a great part of those interviewed has had some kind of experience of the situation, but in a small scale, and few occurrences. It is also believed that this channel may be used to spread the theme, which leads us to conclude that it is viable to the information sharing. Yet, considering the breaking of habits, it is used for a greater involvement of the users. The analysis presents an understanding, and perspectives obtained from the researched theme, broadening horizons to new studies, and deepening the reflections presented in the paper.